Oxford Handbooks Online 2012
DOI: 10.1093/oxfordhb/9780199746521.013.0085
|View full text |Cite
|
Sign up to set email alerts
|

The Employer’s Perspective on Retirement

Abstract: In this chapter we discuss the literature with respect to the role of employers in retirement processes of older workers and provide suggestions for future research. In the first part of this chapter we will review existing theoretical insights regarding the employers' actions and attitudes toward older workers and retirement. In the next section we will discuss empirical findings with regard to age related stereotypes in the workplace and age norms with respect to retirement and present some results form an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…Most studies of the employment of (early) retirees have approached bridge employment from an individual decision-making perspective and have related the type of bridge employment to individual employees' antecedents, such as health, age, and education; and outcomes, such as satisfaction in retirement and with life in general (e.g., Kim & Feldman, 2000;Wang et al, 2008). In comparatively few studies has attention been devoted to the demand side of the labor market and to the crucial role that organizations play in the process of retirement (Henkens & Van Dalen, 2012). Exceptions include the contribution of Hirshorn and Hoyer (1994), who found that almost half of the US organizations they surveyed employed retirees in the early 1990s, although only a fraction had formal policies on the employment of retirees; and the contribution of Karpinska, Henkens, and Schippers (2011), who showed in an experimental study that many managers are reluctant to hire early retirees.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies of the employment of (early) retirees have approached bridge employment from an individual decision-making perspective and have related the type of bridge employment to individual employees' antecedents, such as health, age, and education; and outcomes, such as satisfaction in retirement and with life in general (e.g., Kim & Feldman, 2000;Wang et al, 2008). In comparatively few studies has attention been devoted to the demand side of the labor market and to the crucial role that organizations play in the process of retirement (Henkens & Van Dalen, 2012). Exceptions include the contribution of Hirshorn and Hoyer (1994), who found that almost half of the US organizations they surveyed employed retirees in the early 1990s, although only a fraction had formal policies on the employment of retirees; and the contribution of Karpinska, Henkens, and Schippers (2011), who showed in an experimental study that many managers are reluctant to hire early retirees.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, from a policy perspective, our findings suggest that government may play an important role in developing incentives for both management and labor to reframe employment frameworks, making them more conducive to the retention of retirement-eligible workers. Taking into account the importance of managing the aging population (e.g., with regard to national pension benefits), the role played by national institutions could be a crucial one-shaping organizations willingness to take the steps needed to retain their retirement eligible older workers (Henkens & Van Dalen, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Studies focusing on the organizational context have examined, for example, how organizational policies and supervisor support affect the transition from work into retirement. Another strand of research focuses specifically on the attitudes and behaviors of employers regarding workforce aging (Henkens and Van Dalen, 2012). Research on the country context has focused on the question of how social policy arrangements (e.g., statutory retirement age, employment protection legislation) and socioeconomic conditions (e.g., unemployment rate) affect the retirement transitions of older individuals (e.g., Ebbinghaus and Radl, 2015).…”
Section: Organizational and Country Contextmentioning
confidence: 99%